Data Analytics On Web-Based Document Notification System - Rose Mae U. Reyes, Joana; V. Origines Jr, Domingo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
This study aimed to address the inefficiencies associated with manual document submission by providing and implementing data analytics within a web-based document notification system. The project also aimed to deliver a user- friendly data analytics dashboard, presenting submitted document data through various visualizations such as count metrics, bar graphs, and tables. This approach holds promise in enhancing decision-making processes, operational efficiency, communication, and collaboration within organizations. Descriptive data analytics methodology was employed to effectively summarize and present data points. Moreover, the project adopted the Rapid Application Development methodology for its development. The project received favorable evaluations from its assessors, attaining high ratings with an overall mean score of 4.17 for functionality, 3.95 for reliability, and 3.98 for usability. Consequently, it successfully achieved its objective of integrating descriptive data analytics into the document notification system. This implementation notably benefited the Human Resource Management Office of Davao del Sur State College by furnishing an analytical dashboard equipped with visualizations such as count metrics, bar graphs, and tables. Furthermore, the system facilitated seamless information updates, empowering administrators to make evidence-based decisions and discern trends within their data.